2014
DOI: 10.1186/1297-9716-45-65
|View full text |Cite
|
Sign up to set email alerts
|

Babesia spp. in European wild ruminant species: parasite diversity and risk factors for infection

Abstract: Babesia are tick-borne parasites that are increasingly considered as a threat to animal and public health. We aimed to assess the role of European free-ranging wild ruminants as maintenance mammalian hosts for Babesia species and to determine risk factors for infection. EDTA blood was collected from 222 roe deer (Capreolus c. capreolus), 231 red deer (Cervus e. elaphus), 267 Alpine chamois (Rupicapra r. rupicapra) and 264 Alpine ibex (Capra i. ibex) from all over Switzerland and analysed by PCR with pan-Babesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 46 publications
6
61
1
Order By: Relevance
“…B. venatorum is capable of causing zoonotic disease in immuncompromised humans (Herwaldt et al, 2003) and can infect roe deer, chamois and reindeer (Silaghi et al, 2011;Robert et al, 2008). Among European roe deer, asymptomatic infection appears to be common, as it has recently been recorded in Slovenia (Duh et al, 2005), France (Bastian et al, 2012), Italy (Tampieri et al, 2008;Zanet et al, 2014), Poland (Welc-Falęciak et al, 2013, Switzerland (Michel et al, 2014) and Germany (Overzier et al, 2013). In reindeer, however, clinical babesiosis caused by B. venatorum has been reported in Switzerland (Robert et al, 2008) and in the Netherlands (Kik et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…B. venatorum is capable of causing zoonotic disease in immuncompromised humans (Herwaldt et al, 2003) and can infect roe deer, chamois and reindeer (Silaghi et al, 2011;Robert et al, 2008). Among European roe deer, asymptomatic infection appears to be common, as it has recently been recorded in Slovenia (Duh et al, 2005), France (Bastian et al, 2012), Italy (Tampieri et al, 2008;Zanet et al, 2014), Poland (Welc-Falęciak et al, 2013, Switzerland (Michel et al, 2014) and Germany (Overzier et al, 2013). In reindeer, however, clinical babesiosis caused by B. venatorum has been reported in Switzerland (Robert et al, 2008) and in the Netherlands (Kik et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Babesia divergens is known to cause acute disease in cattle (Bock et al, 2004) and humans (Skrabalo and Deanovic, 1957) and has been claimed to occur in asymptomatic roe deer, red deer, Chamois and Alpine ibex (Capra ibex) in Europe (e.g. Tampieri et al, 2008;Michel et al, 2014;Silaghi et al, 2011). Naturally acquired infection has also been described in reindeer before (Langton et al, 2003), but as mentioned above, the species identity of this sequence provided by Langton et al, (2003) is questionable as stated by Gray et al (2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…capreoli-like infection has been described in chamois (Hoby et al 2009). Several recently published reports have indicated that Babesia infection due to B. capreoli and B. venatorum may have contributed to the mortality of roe deer, reindeer and alpine chamois (Kik et al 2011, Michel et al 2014. Severe infections and Babesia-related mortalities were found in reindeer due to B. divergens and B. odocoilei (see Langton et al 2003, Barlett et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Babesia venatorum has been identified in roe deer, Capreolus capreolus (Linnaeus) (Duh et al 2005, Bonnet et al 2007a. Babesia divergens and B. capreoli have been reported from roe deer, red deer, Cervus elaphus Linnaeus, reindeer, Rangifer tarandus (Linnaeus), alpine chamois, Rupicapra rupicapra (Linnaeus), and alpine ibex, Capra ibex (Linnaeus) (Langton et al 2003, Malandrin et al 2010, Zintl et al 2011, Michel et al 2014. However, the possible role of moose, Alces alces (Linnaeus), as a reservoir for Babesia spp.…”
mentioning
confidence: 99%